Pharmacological Screening of Substituted Benzimidazole Derivatives (Dhaka University Journal of Pharmaceutical Sciences, 2021)
In the present study some substituted benzimidazole derivatives were screened for several biological activities. The synthesized compounds were subjected to evaluation of central analgesic, anti-inflammatory, cytotoxicity, antimicrobial and antioxidant activities by radiant heat induced tail flicking, carrageenan induced rat paw edema inhibition, brine shrimp lethality bioassay, disc diffusion and DPPH free radical scavenging methods, respectively. Compounds 2a, 2c and 2d elongated the tail flicking time by 58.07-, 51.59- and 76.65%, respectively (p < 0.001) at 50 mg/kg body weight dose compared to the standard morphine (87.17%). Compounds 2b, 2c and 2d showed prominent anti-inflammatory activity at 100 mg/kg body weight dose (% of paw edema inhibition 81.75%, 79.09% and 86.69%, respectively) compared to the standard aceclofenac (87.83%). Among the synthesized benzimidazole derivatives, compounds 1a, 1b, 1c, 2a and 2d exhibited potent cytotoxicity with the IC50 values of 5.47-, 11.92-, 4.55-, 7.63- and 7.94 μg/ml, respectively. In addition, compounds 1c and 2d displayed mild to moderate zone of inhibition (8-12 mm). On the other hand, 1a and 1b showed very mild antioxidant activity with IC50 values of 12.25 × 103 μg/ml and 87.33 ×103 μg/ml. Among all the derivatives, 2c, 2d and 1c can be potential candidates for designing new analgesic, anti-inflammatory and anti-cancer agents in future.Dhaka Univ. J. Pharm. Sci. 20(1): 95-102, 2021 (June)